Non-gallstone acute pancreatitis and pre-eclampsia: A case report - Chris Chan; Monika Mukerji (Elsevier, 2018)
Acute pancreatitis is rare but well documented in pregnancy and most cases are attributable to biliary disease. We present a case of acute non-gallstone pancreatitis in a patient with acute and severe pre-eclampsia.A 39-year-old primigravida woman at 33 + 4 weeks' dichorionic diamniotic gestation presented with severe bilateral lower-limb oedema and underwent an emergency caesarean section due to the development of acute severe pre-eclampsia. Postpartum, the woman developed out-of-proportion generalised upper abdominal tenderness with worsening liver function and markedly raised lipase and amylase levels. Imaging confirmed oedema and inflammatory changes in keeping with acute non-gallstone pancreatitis. The patient improved with conservative management and was eventually discharged home on day 13 postpartum.The development of abdominal pain out of proportion to expected clinical progression should prompt the physician to consider other causes, including acute pancreatitis, in order to provide effective and timely clinical care. The clinical presentation of this woman suggests that pre-eclampsia may be associated with the development of acute pancreatitis. Further prospective study would be needed to establish any association. Keywords: Acute pancreatitis, Pregnancy, Pre-eclampsia